A new species of Liolaemus from Añelo sand dunes, northern Patagonia, Neuquén, Argentina, and molecular phylogenetic relationships of the Liolaemus wiegmannii species group (Squamata, Iguania, Liolaemini) - Avila, Luciano Javier; Morando, Mariana; Perez, Daniel Roberto; Sites, Jr., Jack W. (Zootaxa, 2009)
The wiegmannii group of Liolaemus includes L. arambarensis, L. azarai, L. lutzae, L. occipitalis, L. multimaculatus, L. rabinoi, L. riojanus, L. salinicola, L. scapularis, L. wiegmannii, and the species described here. We used sequences of the mitochondrial cyt–b, 12S, and ND4, and the nuclear C–mos gene regions to infer the phylogeny of the majority of the species of the wiegmannii group. We describe a new species that is closely related to L. multimaculatus and L. riojanus, but can be distinguished by a different dorsal coloration, absence of suprascapular spots, and smaller size. Liolaemus cuyumhue sp. nov. lives in marked geographic isolation with respect to other closely-related species of the wiegmannii group.